Search for scalar top quarks in the acoplanar charm jets and missing transverse energy final state in p(p)over-bar collisions at root s=1.96 TeV - Abazovi, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, I.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Cheu, E.; et al. (Elsevier B.V., 2008)
We present a search for the pair production of scalar top quarks, (t) over tilde, using 995 pb(-1) of data collected in p (p) over bar collisions with the Dempty set detector at the Fermilab Tevatron Collider at root s = 1.96 TeV. Both scalar top quarks are assumed to decay into a charm quark and a neutralino ((chi) over tilde (0)(1)), where (chi) over tilde (0)(1) is the lightest supersymmetric particle. This leads to a final state with two acoplanar charm jets and missing transverse energy. We find the yield of such events to be consistent with the standard model expectation, and exclude sets of (t) over tilde and (chi) over tilde (0)(1) masses at the 95% C.L. that substantially extend the domain excluded by previous searches. Published by Elsevier B.V.